2021
DOI: 10.26719/emhj.21.065
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal care experiences of immigrant Syrian women: a qualitative phenomenological study

Abstract: Background: Adverse birth outcomes of immigrant women and neonates are associated with the quality of perinatal care. For this reason, examining immigrant women’s experiences of perinatal care is necessary if host country care systems are to respond appropriately to migration. Aims: The aim of the study was to evaluate the perinatal care experiences of immigrant women. Methods: The qualitative phenomenological design used in the study enabled to make an in-depth exploration of immigrant women's experiences. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
1
3
0
4
Order By: Relevance
“…They have a difficulty in taking blood, someone should teach them". Our findings indicated that perinatal care for immigrant women was partly inadequate and their experiences were not positive, something that came in accordance with other research findings [9]. Respecting women's religion and their cultural elements is one of the most important topics that arose from this interview.…”
Section: Changes-suggestionssupporting
confidence: 89%
“…They have a difficulty in taking blood, someone should teach them". Our findings indicated that perinatal care for immigrant women was partly inadequate and their experiences were not positive, something that came in accordance with other research findings [9]. Respecting women's religion and their cultural elements is one of the most important topics that arose from this interview.…”
Section: Changes-suggestionssupporting
confidence: 89%
“…Os estudos evidenciaram dificuldades econômicas, falta de apoio social, problemas de locomoção e de comunicação com baixo letramento junto aos profissionais de saúde. A xenofobia, as diferenças culturais e a barreira do idioma representaram os principais desafios e interferiu negativamente na experiência da gestação (Abdin, 2018;Ahmed et al,2017;Henry et al, 2020;Dadras et al, 2020;Vurgec et al, 2021;Owens et al, 2016;Riggs et al, 2020).…”
Section: Discussionunclassified
“…Dois estudos com refugiadas e migrantes desta revisão apresentaram iniciativas pontuais de sucesso que favoreceram o acesso delas aos serviços de saúde como, por exemplo, a implantação de sistemas de apoio que obtiveram resultados satisfatórios ao proporcionarem maior adesão de mulheres à amamentação e outro programa que ofereceu assistência de saúde a mulheres refugiadas que desejaram abortar de forma segura e assistida (Bektas & Arkan, 2021;Vurgec et al, 2021).…”
Section: Discussionunclassified
See 2 more Smart Citations